2021
DOI: 10.3389/fvets.2021.681951
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Supplementation With a Powder Containing A.N. ProDen™ (Ascophyllum Nodosum) Algae on Dog Saliva Metabolome

Abstract: The objective of this placebo-controlled, double-blind, randomized study (designed according to evidence-based medicine standards) was to determine the effect of 30-day administration of powdered brown algae, Ascophyllum nodosum (ProDen PlaqueOff, SwedenCare AB, Sweden), on saliva metabolomes in dogs. Sixty client-owned dogs underwent professional dental cleaning and were randomly subdivided into two groups receiving daily powdered brown algae A. nodosum, or a placebo (microcrystalline cellulose in powder), ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The association between plaque formation and calculus reduction and the improvement of oral health was the highest during the first 30 days of the treatment and less remarkable thereafter. Although the exact mechanism of its action is still unclear the results of our studies suggest that brown algae change the composition of saliva in supplemented dogs by inhibition or turning off some pathways that could enhance plaque or calculus development (Gawor et al 2021). While the preventive action of Ascophyllum nodosum on dental deposit accumulation is significant, the curative action of the kelp on existing plaque and calculus is insufficient.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The association between plaque formation and calculus reduction and the improvement of oral health was the highest during the first 30 days of the treatment and less remarkable thereafter. Although the exact mechanism of its action is still unclear the results of our studies suggest that brown algae change the composition of saliva in supplemented dogs by inhibition or turning off some pathways that could enhance plaque or calculus development (Gawor et al 2021). While the preventive action of Ascophyllum nodosum on dental deposit accumulation is significant, the curative action of the kelp on existing plaque and calculus is insufficient.…”
Section: Discussionmentioning
confidence: 81%
“…The group of cats with the uncleaned teeth model (curative usage) showed reduction of plaque and calculus formation after 30 days of observation at 3.1 and 8.8%, respectively (Gawor and Jank 2019). These findings suggest that the curative effects of Ascophyllum nodosum supplementation are not remarkable, and this product should be rather a part of home care strategy following professional dental cleaning (preventive usage) than an exclusive treatment modality.…”
Section: Summary Of Clinical Datamentioning
confidence: 85%
See 2 more Smart Citations
“…Our results suggest that seaweed may have potential anti-parasitic activity when included as a functional feed component in canine diets. Previous studies have included seaweeds in dog foods for different potentially beneficial effects [44][45][46][47]. Pinna et al found that ingestion of intact seaweeds at an inclusion level of 15 g/kg diet was well tolerated by the dogs and did not alter the apparent total tract nutrient digestibility in their study [47].…”
Section: Discussionmentioning
confidence: 96%